Formulasi Dan Uji Pelepasan Pada Mikroemulsi Ovalbumin Sebagai Sistem Penghantaran Protein - Ida Kristianingsih (JURNAL FARMASI GALENIKA, 2015)
Microemulsions are thermodynamically stable colloidal dispersions of water and oil stabilized by a surfactant and a cosurfactant. The aim of the present study was to developmicroemulsion as a protein delivery based on proteins released by using ovalbumin (OVA) as a model protein. W/O microemulsion with the concentration ratio of surfactant (Tween 80-Span 80) cosurfactant (butanol) 5:1, 6:1, 7:1 were investigated. All formulation showed similarity organoleptic (yellow, transparent, low viscosity). Ovalbumin release test were analyzed using UV-Vis spectrophotometric method at wavelength 584 nm. Comomassie Brilliant Blue (CBB) were use detection of ovalbumin. Franz diffusion cells with the cellophane membraneswere used. The amount of released OVA was measured with UV-spectrophotometric and the percentage of drug released was calculated. The highest AUC of released ovalbumin from microemulsion were formula 5:1. Based on the results obtained that the w/o microemulsion 5:1 could be used as a possible alternative to protein delivery system. Keywords : Kata kunci :